The NOD2 receptor is crucial for immune responses towards New World Leishmania species. Issue 1 (December 2017) - dos Santos, Jéssica; Damen, Michelle; Oosting, Marije; Jong, Dirk; Heinhuis, Bas; Gomes, Rodrigo; Araújo, Carla; Netea, Mihai; Ribeiro-Dias, Fátima; Joosten, Leo
Abstract American Tegumentary Leishmaniasis is a chronic infection caused byLeishmania protozoan. It is not known whether genetic variances in NOD-like receptor (NLR) family members influence the immune response towardsLeishmania parasites and modulate intracellular killing. Using functional genomics, we investigated whether genetic variants inNOD1 orNOD2 influence the production of cytokines by human PBMCs exposed toLeishmania . In addition, we examined whether recognition ofLeishmania by NOD2 contributes to intracellular killing. Polymorphisms in theNOD2 gene decreased monocyte- and lymphocyte-derived cytokine production after stimulation withL. amazonensis orL. braziliensis compared to individuals with a functional NOD2 receptor. The phagolysosome formation is important forLeishmania -induced cytokine production and upregulation ofNOD2 mRNA expression. NOD2 is crucial to control intracellular infection caused byLeishmania spp. NOD2 receptor is important forLeishmania recognition, the control of intracellular killing, and the induction of innate and adaptive immune responses.